(x-1)^2 is the factored version, so vertex is at 0, which is 1, so, A
Answer:
D
Step-by-step explanation:
f(x) = 10x - 5 → x = 10g(x) - 5 → x + 5 = 10g(x) →
g(x) = (x + 5)/10
Answer:
D.(1, -1, 2) hope this helps
Okay so the first thing you need to do is move the all the variables to one side of the equal sign
Thanks for posting your question here. The answer to the above problem is x = <span>48.125. Below is the solution:
</span>
x+x/7+1/11(x+x/7)=60
x = x/1 = x • 7/7
x <span>• 7 + x/ 7 = 8x/7 - 60 = 0
</span>x + x/7 + 1/11 <span>• 8x/7 - 60 = 0
</span>8x <span>• 11 + 8x/ 77 = 96x/ 77
</span>96x - 4620 = 12 <span>• (8x-385)
</span>8x - 385 = 0
x = 48.125